3-Hydroxy-3-p-Tolyl-1-o-Nitrophenyhl Triazene in Spectrophotometric Determination of Nickel - Bhatt, Rekha; Goswami, A.K.; Tyagi, M.P.; Purohit, D.N. (Asian Journal of Chemistry, 2010)
Results of spectrophotometric determination of nickel with 3-hydroxy-3-p-tolyl-1-o-nitrophenyl triazene are reported here.